The Relationship of Parental Overprotection and Care With Anger, Stress and Psychological Wellbeing - Kaur, Sukhpreet (My University, 2023)
This study aimed to study the role of parental overprotection and care on anger, stress and psychological wellbeing among young adolescents (18-25). A sample of 199 students participated in this study, through online survey and some responses were collected through offline mode. Correlation design was adopted. Measures like parental bonding inventory, Clinical anger scale, Perceived stress scale and psychological wellbeing scale used.
Keywords: Father overprotection; Father care; Mother overprotection; Stress; Mother car Anger; Psychological wellbeing